(untitled) (Acta Scientiarum. Biological Sciences, 2014)
Fifty-six villages along the coast of the State of Paraíba, Brazil, were visited to determine and map the occurrence of Amazona amazonica (Linnaeus, 1766). Search was conducted with binoculars and the residents of each locality were interviewed using a questionnaire to obtain information about the occurrence and species´s biological data. Reports of recent and old occurrences, absence and feeding areas were registered. The food items mentioned were fruits, such as cashew, cashew nuts, palm oil, and agricultural products, such as corn. The reproductive period occurred between November and December. Breeding sites were mangrove areas and coconut trees, with nests being made in tree hollows. Questionnaires helped to elaborate a distribution map of the species, in which the actual distribution was based on visual records, whilst the potential distribution of the species was based on the questionnaire answers. Furthermore, they provided an overview of the biology of the species in agreement with that reported in the literature. Current data may be used in future studies on the conservation of the species in the State of Paraíba.